Determinan Sikap Dalam Penggunaan Sistem Keuangan Desa (Siskeudes) - Dinda Amelia Kusumastuti; Rihan Mustafa Zahri (Universitas PGRI Madiun, 2020)
SISKEUDES application is an application developed by BPKP to improve the quality of village financial governance that must be implemented. The implementation of regulations, the success of the purpose of the application of SISKEUDES will determine the effectiveness of the system. The successful implementation of the system is seen from the attitude of the village government in using the system. This research aims to test the perception of usability, perception of ease of use, subjective norms, and complementary to the attitude of use of rural financial system (SISKEUDES) applications. This study used survey methods and took samples in the village government of Madiun Regency and Kediri Regency which positioned as users of SISKEUDES application as many as 230 respondents. Data that has been disseminated through questionnaires is analyzed using partial least square (PLS) based structural models with SmartPLS software version 2.0. The results of this study prove that the user attitude of SISKEUDES application is positively influenced by perception of usability, subjective norms, and compatibility in using SISKEUDES applications. The study found the perception of ease of use had no effect on the attitudes of SISKEUDES application users.Keywords; Perception of Usability; Perception of Ease of Use; Subjective Norms; Compatibility; Attitude